Neurorrhaphy of the sciatic nerve with autologous sural nerve graft in a gunshot wound: a case report - Serrano, Erik B.; Serrano, Beatriz R.; Leyva, Amador J.; Vaca, Julio C. A. (International Journal of Research in Medical Sciences, 2024)
Motor and sensory nerve injuries in the lower limb have been on the rise due to the increase in traffic accidents, injuries caused by third parties, injuries caused by sharp weapons or firearm projectiles, causing severe impairment of the functionality of the limb by affecting sensitivity, motor skills or both. In our manuscript we describe the case of a 37-year-old female patient with severe injury to the right greater sciatic nerve of the axonotmesis type secondary to a gunshot wound, presenting total loss of sensitivity and motor skills of the right lower extremity, undergoing neurorrhaphy of the sciatic nerve with autologous graft of the sural nerve with motor and sensory recovery of almost 50% in a short period. When considering surgical treatment for nerve injury, various factors related to the surgical technique as well as the patient’s clinical condition must be considered. Autologous nerve grafting is the gold standard for nerve repair. The sural nerve is a common candidate and is considered the workhorse graft.